Dinâmica e fragilidade ambiental na paisagem da microbacia hidrográfica do rio Paripueira, Sergipe - Melo, Isabela Santos de (2018)
The water catchment area of the Paripueira river is located in the municipality of Itaporanga d'Ájuda, Sergipe, and stands out as a space unit in which socio-environmental interactions are expressed in the management of water resources and in land use. In this sense, this research has as main objective, among other aspects, to analyze the integrated environmental dynamics, based on the characterization of the landscape units and the evaluation of the environmental fragility of the study area. In order to achieve the proposed objectives, some methodological procedures were carried out, such as bibliographical and cartographic data collection, thematic maps elaboration; and field work. Based on the theoretical systemic framework, this study had as a methodological contribution the geosystemic and ecodynamic models, associated with the assumption of evaluation of potential and emerging environmental fragility. The results of this study demonstrate that the microbasin presents different levels of environmental fragility according to the characteristics of the natural components and the degree of antropic intervention. Despite the limited human occupation, the landscape of the study area has been gradually modified due to the development of shrimp farming, extensive livestock farming, coconut cultivation and, above all, mining, leading to the decharacterization of landscape through the clearing of hills, suppression of vegetation cover, and occurrence of erosion and silting processes in some parts of the watercourses. Thus, the present study ratifies the importance of studies in small basins, and should serve as a subsidy for the formulation of planning policies and territorial management that benefit the quality of life of the local population and lessen the environmental problems that cover area.